Management of Fournier’s Gangrene at postgraduate medical institute Sandeman provincial Hospital Quetta - Anwar Lehri; Muhammad Iqbal Khan Khan; Riffat Arbab; Lailama Shah; Shabir Ahmed Lehri; Hafsa Jaffar (Journal of University Medical & Dental College, 2022)
BACKGROUND & OBJECTIVE: Fournier's Gangrene is a quick development of necrotizing, fulminant infection of the scrotum, perineum, and lower abdominal wall and can  involve the groin. Synergic aerobic and anaerobic organisms can cause this disease. The aim of this study is to evaluate the causes, complications and optimal treatment of Fournier’s Gangrene.METHODOLOGY: A total of 150 patients were included. Fournier’s Gangrene was diagnosed clinically. Detailed clinical examination was performed, and the complications and modes of treatment were recorded. Calculation of descriptive statistics was done by the stratification and application of independent T-test and Chi-square test wherever applicable for post-stratification, considering p-value ≤0.05 as significant.RESULTS: The mean age was 31.74±6.24 years. The most common presenting complaint was the dusky appearance of the overlying skin. In the diabetic group, (66)44% had intense genital pain and tenderness, while in the non-diabetic group (72)48% observed a dusky appearance of the overlying skin and (37)24.7% had morbid obesity. No significant association was found between mortality of study groups, their age groups and their duration of hospital stay.CONCLUSION: Most common presenting complaint was the dusky appearance of the overlying skin. The anal abscess was the most common etiology, followed by a strangulated inguinal hernia. The mortality rate was 24%.